Detecting colorectal cancer using electrical impedance spectroscopy: an ex vivo feasibility study. (22nd May 2017) - Pathiraja, Angela; Ziprin, Paul; Shiraz, Arsam; Mirnezami, Reza; Tizzard, Andrew; Brown, Brian; Demosthenous, Andreas; Bayford, Richard
Abstract: Objective . Colorectal cancer is the fourth most common cancer worldwide, with a lifetime risk of around 20%. Current techniques do not allow clinicians to objectively assess tissue abnormality during endoscopy and perioperatively. A method capable of objectively assessing samples in real time and which can be included in minimally invasive diagnostic and management strategies would be highly transformative. Electrical impedance spectroscopy (EIS) may provide such a solution. This paper presents a feasibility study on using EIS in assessing colorectal tissue. Approach . We performed tetrapolar EIS using ZedScan on excised human colorectal tumour tissue and the matched normal colonic mucosa in 22 freshly resected specimens following elective surgery for colorectal cancer. Histopathological examination was used to confirm the final diagnosis. Statistical significance was assessed using the Wilcoxon signed rank test. Main results . Tetrapolar EIS could discriminate cancer with statistically significant results when applying frequencies between 305 Hz and 625 kHz ( p   <  0.05). 300 Ω was set as the transfer impedance threshold to detect cancer. Thus, the area under the corresponding receiver operating characteristic curve for this threshold was 0.7105. Significance . This feasibility study demonstrates that impedance spectra changes in colorectal cancer tissue are detectable and may be statistically significant, suggesting that EIS has the potential to be the core technology in a novel non-invasive point of care test for detecting colorectal cancer. These results warrant further development by increasing the size of the study with a device specifically designed for colorectal cancer.